Analysis of the Implementation of Private Entity Financial Accounting Standards in the Presentation of Financial Statements of PT BPRS Puduarta Insani - Tanjung, Nur Khafifah; Syafina, Laylan; Samri Juliati Nasution, Yenni (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the Analysis of the Application of Private Entity Financial Accounting Standards (SAK EP) in the Presentation of Financial Statements of PT BPRS Puduarta Insani. The preparation of SAK EP is intended to meet the financial reporting needs of private entities, where the entity is not accountable to the public so that the publication of reports is intended for the general public. The data analysis method in this study is descriptive with a case study based on secondary data from the financial statements of PT BPRS Puduarta Insani. Based on the analysis that has been presented in the discussion above, it can be concluded that The entity at BPRS Puduarta Insani has presented complete financial statements in accordance with the Financial Accounting Standards for Private Entities (SAK EP), namely the balance sheet, income statement, statement of changes in equity, statement of cash flows, and notes to the financial statements. In the notes to the financial statements, there is a statement that the financial statements are prepared in accordance with SAK EP, which is intended to ensure that the financial statements fairly present the financial position, performance, and cash flows, so that the objectives of the financial statements can be achieved. This statement explains that the BPRS has prepared financial statements by applying the rules in accordance with SAK EP.